Pour une observation filmique des pratiques cliniques de l’acupuncture - Lucia Candelise; Gilles Remillet (Anthropologie & Santé)
From the cinematographic device to that of the therapeutic relationship, this contribution places the filmic investigation at the heart of the medical practice of acupuncture. It aims to evoke the ways in which film makes it possible to apprehend in a single gesture the experience of care and that of ethnographic fieldwork immersion